Adamantane Resistance in Seasonal Human Influenza A Viruses from Calgary, Alberta (January 2007 to August 2008) - Kanti Pabbaraju; Sallene Wong; Dmitri K Kits; Julie D Fox (Canadian Journal of Infectious Diseases and Medical Microbiology)
The available antivirals for the treatment and prophylaxis of influenza A infections include the adamantanes (amantadine and rimantadine), which are matrix (M2) protein inhibitors, and the neuraminidase inhibitors (oseltamivir and zanamivir). Resistance to the adamantanes is conferred by mutations at amino acid positions 26, 27, 30, 31 or 34 within the M2 protein of influenza A viruses. A significant increase in adamantane resistance has been reported worldwide since 2003, reflected by a similar increase in Canada. The present study reports on the frequency of adamantane resistance in seasonal influenza A viruses in Calgary, Alberta, for the period between January 2007 and August 2008, as an update to the previous report. Positive influenza A samples (221 original patient specimens and 34 isolates obtained by viral culture) were analyzed for changes in the critical amino acid residues of the M2 gene. The amplification and sequencing of regions that confer adamantane resistance directly from RNA extracts of clinical samples (without previous culture) makes this approach a fast and efficient process for monitoring resistance. The results showed that the frequency of resistance varied from 37.5% to 49.2% in circulating influenza A H3N2 virus strains (n=213) between January 2007 and April 2007. The frequency of resistance increased to 100% in May 2007, after which all H3N2 viruses were resistant until the end of the monitoring period. All resistant H3N2 viruses contained the serine to asparagine substitution at amino acid position 31. Resistance was not observed in the H1N1 viruses tested (n=39) within this monitoring period. The level of adamantane resistance in H3N2 viruses continues to remain high since resistant viruses became the prevalent circulating strains in 2005. Recent reports have indicated that the currently circulating swine-origin influenza A H1N1 subtype viruses are adamantane resistant. It is, thus, important to continue to monitor seasonal influenza A viruses for antiviral resistance markers to ensure optimal prophylaxis and treatment.